The El Dorado of handball? Foreign female players stay, while domestic players return from abroad - Bon, M.; Doupona Topic, M.; Sibila, M. (Journal of Human Kinetics, 2016)
The main purpose of this research was to study the characteristics of migration in European women`s handball based on the Slovenian example and to find the differences between the foreigners coming to Slovenia and the Slovenians transferring to foreign clubs. The research was based on 16 open face-to-face semi-structured interviews (8 Slovenians (age 29.5 ± 6.2 years) and 8 foreigners (age 35.5 ± 8.7 years)). We found out that the most powerful factor in foreigners was the financial one, while within Slovenian players it was their personal desire for progression within their sport, the club`s reputation and poor conditions in their previous club. The results confirm that when making a decision on transfer, all players had the support of family and friends, while the clubs of foreign players were not as supportive. Most interviewees considered their careers successful and did not regret going abroad. The research indicates that the largest differences discovered between Slovenians and foreigners were that foreign female players chose to stay in the new country (Slovenia), while domestic players returned home after few years playing abroad. In conclusion, the results show that in top-level handball there are important differences between migration models which are based on nationality and also that the migration models change throughout time, which is largely connected with the socioeconomic events in the country of origin or transfer.